Behavioral and Acoustic Responses of the Oriental Reed Warbler (Acrocephalus orientalis), at Egg and Nestling Stages, to the Common Cuckoo (Cuculus canorus) - Wang, Jiaojiao; Ma, Laikun; Chen, Xiangyang; Yang, Canchao (Frontiers in Ecology and Evolution, 2021)
Cuckoo nest parasites lay eggs in host nests and thereby transfer all reproduction costs to the hosts. This greatly reduces host fitness. Parasitism has selected for the evolution of anti-parasitic strategies in hosts, including nest defense. The dynamic risk assessment hypothesis holds that nest parasitism only threatens the nests during the egg stage, so hosts should reduce the level of defense against nest parasites after the egg stage. We studied the behavioral and acoustic responses of oriental reed warblers (Acrocephalus orientalis), during both the egg and nestling stages, toward the common cuckoo (Cuculus canorus), sparrowhawks (Accipiter nisus) and oriental turtle doves (Streptopelia orientalis). A. orientalis can visually distinguish cuckoos from sparrowhawks and doves, indicating that hawk mimicry did not work for the cuckoos. The behavioral response of hosts in the nestling stage was stronger than in the egg stage, which supports the offspring value hypothesis and suggests that cuckoos may also act as nest predators. However, there was no difference in the alarm calls A. orientalis produce in response to different invaders, indicating that different types of alarm calls may not contain specific information.